The effect of real earnings management through operating cash flow approach on company performance - Soni Agus Irwandi (The Indonesian Accounting Review, 2014)
Earnings management through real activities is a numbers game with the profits made through the activities associated with operational activities. In this study, real earnings management with operating cash flow approach using proxies on firm performance indicators Return on Assets (ROA) and Tobin's Q. The sample used in this study is a manufacturing company using the sample selection criteria. The results of the regression analysis for this study indicate that real earnings management approach to operating cash flow effect on the company's performance indicators Return on Assets (ROA) and no effect on the company's performance indicators Tobin's Q.